2-Dodecyl-6-Methoxycyclohexa-2,5-Diene-1,4-Dione Ameliorates Diabetic Cognitive Impairment Through Inhibiting Hif3α and Apoptosis - Wang, Lihui; Cao, Jinjin; Xu, Qianqian; Lu, Xiaomei; Yang, Xin; Song, Qiong; Chen, Shuai; Du, Kechen; Huang, Renbin; Zou, Chunlin (Frontiers in Pharmacology, 2021)
2-Dodecyl-6-Methoxycyclohexa-2, 5 -Diene-1,4-Dione (DMDD) was purified from the roots of Averrhoa carambola L. Previous research demonstrated that DMDD is a small molecular compound with significant therapeutic potential for diabetes. However, the efficacy of DMDD to ameliorate diabetic cognitive impairment in type 2 diabetes mice has not been reported. In present study, we detected gene expression profiles in the hippocampi of diabetic db/db mice after DMDD treatment. 9-week-old male db/db mice were treated with DMDD (50 mg/kg) for 28 days followed by Y maze and novel object recognition test for behavioral evaluation. Our results showed that DMDD attenuated the spatial working memory and object recognition memory impairment in db/db mice. Using mouse lncRNA array analysis, 11 lncRNAs and 4 mRNAs with significant differential expression were identified after DMDD treatment. Among these, Hif3a expression was significantly increased in the hippocampi of diabetic db/db mice compared with db/m control mice and then decreased after DMDD treatment. Besides, DMDD treatment reduced tau protein expression, the formation of a-synuclein oligomers and high glucose-induced apoptosis in the hippocampi of db/db mice and high glucose-treated HT22 cells. DMDD protected neural cells from apoptosis by repression of Hif3a. These data suggest that DMDD can alleviate cognitive impairment by regulating apoptosis through the pro-apoptotic protein Hif3a. In conclusion, our study suggests that DMDD has great potential to be a new preventive and therapeutic compound for diabetic cognitive impairment.